Sensitivity of Escherichia coli Bacteria Towards Antibiotics in Patient with Diabetic Foot Ulcer - Sari, Rafika; Apridamayanti, Pratiwi; Puspita, Indira Diah (UI Scholars Hub, 2018)
Chronic complication of diabetes mellitus is diabetic foot ulcers. Diabetic foot ulcer can be defined as an open wound in the feet which will become infected as the result of high blood sugar levels that develops and become place of bacteria. One of the bacteria in diabetic foot ulcer is Escherichia coli. Imprecise use of antibiotics in the treatment of diabetic foot ulcers can cause antibiotic resistance to bacteria. This study aims to determine antibiotic sensitivity of Escherichia coli bacteria in diabetic foot ulcer Wagner grade III and IV. Samples of diabetic foot ulcer swab’s with Wagner grade III and IV were taken as Consecutive sampling. Identification of Escherichia coli bacteria is done by using a biochemical test and Gram stain test. Antibiotic sensitivity test is conducted by using Kirby Bauer’s disc of diffusion method. Escherichia coli bacteria that were tested are sensitive to amikacine, gentamicine, ciprofloxacin, levofloxacine, ceftriaxone, cefotaxime, imipenem and meropenem antibiotics but showed resistant to cefadroxil.